Symbolic and Imaginative Source of Mudra and Asana in Buddhist Art - Demenova, Victoria V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article reveals the meaning of one of the key elements of Buddhist iconography, i.e. the phenomenon of mudra (folding of fingers) and asana (body posture). The author analyses the terminological diversity of the designation of mudra and associated meanings in research literature, as well as the history of this phenomenon in the culture of India as a source of formation of the principles of Buddhist iconography and imagery. Based on the etymological analysis given by D. Todaro and the history of the development of the phenomenon of mudra and asana in the art of Buddhism, these only externally similar phenomena in Indian culture in general and Buddhist art are distinguished. Additionally, the author highlights the semantic connotations of gesture and asana in images of Buddha Shakyamuni, associated with the historical context, and the further diversity of this phenomenon in the iconography of bodhisattvas, associated with the internal aspects of the teachings of Buddhism. The meaning of gesture in the practice and art of Tantrism is discussed separately. The author puts forward the thesis that gesture and asana in Tantrism are the key to understanding this phenomenon in the art of Buddhism in general, including images earlier than tantric images. Referring to several sculptural images of Buddhas and bodhisattvas, which are considered masterpieces of Buddhist art (museums of India and Mongolia), whose iconography includes similar mudras and asanas, the author shows, analyses and describes the diversity of the artistic image that is born within the same iconography with regard to the artistic historical manner in which there is a difference between the symbolic essence of a gesture (mudra) and body position (asana) and their artistic images.